2000
DOI: 10.1006/jcph.2000.6534
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Annealing Clusterization Algorithm for Studying the Multifragmentation

Abstract: We here present the details of the numerical realization of the recently advanced algorithm developed to identify the fragmentation in heavy ion reactions. This new algorithm is based on the simulated annealing method and is dubbed the simulated annealing clusterization algorithm (SACA). We discuss the different parameters used in the simulated annealing method and present an economical set of the parameters which is based on the extensive analysis carried out for the central and peripheral collisions of Au-Au… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(76 citation statements)
references
References 26 publications
2
74
0
Order By: Relevance
“…This finding is in agreement with the results reported in Refs. [6,15], where it was found that NN cross-section has sizable effect on reaction dynamics. Note that in these studies, static equation of state was used.…”
Section: Results Of Multifragmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in agreement with the results reported in Refs. [6,15], where it was found that NN cross-section has sizable effect on reaction dynamics. Note that in these studies, static equation of state was used.…”
Section: Results Of Multifragmentationmentioning
confidence: 99%
“…In the very low incident energy region, the nuclear structure, determination of fusion cross sections, synthesis of super heavy elements takes place [1,2], while from low to intermediate incident energy region, the dominant phenomena's are multifragmentation, collective flow, balance energy, elliptical flow, transition energy, liquid gas phase transition and particles production (pion, kaon, Σ) etc. [3][4][5][6][7][8][9].The high energy region deals with the phenomena of Quark Gluon Plasma (QGP), which is generated by STAR as well as LHC experimental collaborations [10,11]. There are different theoretical models developed time to time for the study of these phenomena's.…”
Section: Introductionmentioning
confidence: 99%
“…One of the important aspects in fragmentation is the stability of the fragments as well as the nucleons surrounding a fragment. The change in the nucleon content of the fragments between two successive time steps can be quantified with the help of the persistence coefficient [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…This idea was launched by Dorso et al [3] and it has been developed into the Simulated Annealing Clusterisation Algorithm (SACA) [4].…”
Section: Phqmd+friga Modelmentioning
confidence: 99%